Acute Pancreatitis Following Endoscopic Ampullary Biopsies without Attempted Cannulation of the Ampulla of Vater - Spyridon Michopoulos; Dimitra Kozompoli; Sparti Ntai; Georgios Kalantzis; Evanthia Zampeli; Kalliopi Petraki (Korean Society of Gastrointestinal Endoscopy, 2016)
A 51-year-old man underwent diagnostic work-up for an abnormal-appearing ampulla of Vater. Three hours after biopsy of the ampulla, the patient presented with intense symptoms suggesting acute pancreatitis, which was later confirmed with laboratory and radiographic examinations. Other causes were excluded and the acute pancreatitis was considered a procedural complication. This is a rarely reported complication that must be taken into consideration when biopsies are performed in the ampulla of Vater.